Responses of Water and Pigments Status, Dry Matter Partitioning, Seed Production, and Traits of Yield and Quality to Foliar Application of GA3 in Mungbean (Vigna radiata L.) - Islam, Mohammad Sohidul; Hasan, Md. K.; Islam, Bushra; Renu, Nowrin Akhter; Hakim, Mohammad A.; Islam, Mohammad Rafiqul; Chowdhury, M. Kaium; Ueda, Akihiro; Saneoka, Hirofumi; Ali Raza, Muhammad; Fahad, Shah; Barutçular, Celaleddin; et al. (Frontiers in Agronomy, 2021)
This study evaluated the role of gibberellic acid [GA3; (0, 100, 200, and 300 ppm)] in modulation of the growth, physiology, yield, and quality traits in two varieties (BARI Mung-6 and BARI Mung-8) of mungbean (Vigna radiata L.). Irrespective of the two varieties (BARI Mung-6 and BARI Mung-8), 100, 200, and 300 ppm of GA3 differentially modulated the tested parameters (relative water content, RWC; photosynthetic pigments: chlorophyll a, chlorophyll b, and carotenoids; growth parameters: fresh and dry weights of leaves, petioles, stems, and roots; yield contributing traits such as plant height, number of pods plant−1, number of grains pod−1, pod length, and 100-grain weight; quality traits such as grain nitrogen and protein). However, compared to the lowest GA3 (100 ppm) and the highest GA3 (300 ppm), the moderate concentration of GA3 (200 ppm) led to highest values of leaf-RWC, where this parameter exhibited 16.1 and 13.4% increase in BARI Mung-8 and BARI Mung-6, respectively. Similarly, the tested herein growth parameters and the yield traits significantly increased up to the foliar application of the moderate GA3 concentration (200 ppm), and thereafter these traits decreased with 300 ppm GA3. The 200 ppm-led changes in the growth and yield traits were significantly higher in BARI Mung-8 when compared to BARI Mung-6. Considering the quality traits, GA3 positively influenced the nitrogen and protein content in grains, where 200 ppm of GA3 led to increases of 25.2% in N, and 17.7% in protein over control in BARI Mung-6; whereas, BARI Mung-8 exhibited 28.3% in N, and 18.3% in protein with 200 ppm GA3 over control. Overall, BARI Mung-8 significantly responded to the foliar supply of 200 ppm GA3 when compared to BARI Mung-6. Hence, in order to high yield and grain protein content, the application of 200 ppm GA3 may be applied in V. radiata before and during flowering. The major mechanisms underlying the responses of the water relation, growth, and yield traits to the GA3 concentrations need to be explored.